2008
DOI: 10.1158/1078-0432.ccr-07-4045
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Expression of CXCL5 in Colorectal Cancer Is Associated with Rapid Tumor Formation in Rats and Poor Prognosis in Patients

Abstract: Purpose: We isolated a subline (CC531M) from the CC531S rat colon carcinoma cell line, which grows and metastasizes much more rapidly than CC531S. We found, using RNA expression profiling, that one of the major changes in the CC531M cell line was a 5.8-fold reduction of the chemokine CXCL5. The purpose of this study was to determine the effect of CXCL5 expression on colorectal tumor growth and metastasis. Experimental Design: CC531 clones were generated with either knockdown or restored expression of CXCL5. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 44 publications
4
32
1
Order By: Relevance
“…However, the preponderance of evidence showed that chemokines contribute mainly to carcinogenesis in the progress of cancers (19). Although CXCL5 has been reported to have numerous roles in carcinomas (20,21), to the best of our knowledge, the present study was the first to conduct a paracrine secretion assay to investigate the effects of endogenous CXCL5 secreted by hepatic stellate LX-2 cells on the oncogenic potential of HB HepG2 cells. HepG2 was originally thought to be a hepatocellular carcinoma cell line and was utilized to investigate hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 91%
“…However, the preponderance of evidence showed that chemokines contribute mainly to carcinogenesis in the progress of cancers (19). Although CXCL5 has been reported to have numerous roles in carcinomas (20,21), to the best of our knowledge, the present study was the first to conduct a paracrine secretion assay to investigate the effects of endogenous CXCL5 secreted by hepatic stellate LX-2 cells on the oncogenic potential of HB HepG2 cells. HepG2 was originally thought to be a hepatocellular carcinoma cell line and was utilized to investigate hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 91%
“…CXCL5 high patients had lower OS and DFS rates compared with CXCL5 low patients. In contrast, Frank et al demonstrated that the absence of CXCL5 expression in tumor tissues was correlated with poor prognosis in CRC, and they also found that CXCL5 was overexpressed in tumor tissues [22]. They attributed these phenomena to intratumoral infiltration of T cells and neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…The CXCL5 expression has been shown to be elevated at both mRNA and protein levels and affect patients’ survival in a number of human tumors, including in pancreatic [31, 33], colorectal [34], breast [35], ovarian [36], or prostate [30] carcinomas. However, survival data are limited and inconsistent [31, 3739]. In the study of White et al, risk of the recurrence after lung cancer resection in NSCLC patients’ was found to be associated with enhanced expression of the sum angiogenic CXC chemokines [12].…”
Section: Discussionmentioning
confidence: 99%